Flavonoids from Macaranga lowii - Widiastuti Agustina; Lia D. Juliawaty; Euis H. Hakim; Yana M. Syah (Journal of Mathematical and Fundamental Sciences, 2012)
A new isoprenylated dihydroflavonol derivative, macalowiinin (1), together with two known flavonoids 4'-O-methyl-8-isoprenylnaringenin (2) and 4'-O-methyl-5,7,4'-trihydroxyflavone (3) (= acasetin), have been isolated from the methanol extract of the leaves of Macaranga lowii. The structures of these compounds were determined based on UV, NMR, and mass spectral data, and optical rotation. Preliminary cytotoxic evaluation of compounds 1 "“ 3 against P-388 cells showed that compound 3 is the most active with IC50 was 58.7 mM.